PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM IMPLEMENTASI BUDAYA KERJA SEWAKADHARMA DI LINGKUNGAN PEMERINTAH KOTA DENPASAR - Anak Agung Sagung Kartika Dewi (Forum Manajemen STIMI Handayani Denpasar, 2021)
Denpasar City Government has established Sewakadharma as the work culture of the entire apparatus by adopting Hindu religious values and Balinese culture, namely sudharma, sudira, susatya, subrata, and susila. Human resource management plays an important role in the implementation of the Sewakadharma work culture in the Denpasar City Government. Through a qualitative study that is based on content analysis of Denpasar Mayor Regulation Number 38 of 2018, the role of human resource management is to encourage the creation of Sang Sewakadharma, which is an apparatus capable of implementing the values of the Sewakadharma work culture. Human resource management includes aspects of policy influence, the flow of apparatus utilization, reward systems, and work systems in realizing Sang Sewakadharma.